Pelatihan Kemampuan Berbahasa Inggris (Speaking) dengan Menggunakan Strategi IELTS Bagi Mahasiswa Sastra Cina di Universitas Sumatera Utara (USU) - Muhammad Kiki Wardana; Wan Anayati; Mayasari Mayasari (JPM: Jurnal Pengabdian Masyarakat, 2020)
This training aims to improve students' skills in taking the EITLS simulation test, especially speaking. This training has shown quite good skills because there are some students who are able to achieve a score range of 7, and most of the test participants are also in the 5-6 range, only a few students are in the 4-5 range. The practice factor is the main factor affecting the success of test takers to improve their skills in speaking English, however, all students interviewed stated that they did not make special preparations when they were going to do the test, so the results they obtained still needed to be improved. Anxiety during the speaking test affects the test taker's skills in answering the questions given, besides that the test taker's difficulty in understanding some of the meanings of the words spoken by the examiner makes it difficult for the test taker to respond to the questions asked, but knowing tips and tricks in carrying out the speaking test can minimize the things that can interfere during the test execution.